'Community-Case-Study-Reports' of 'Spices-Community-Biomedicines-Physiology' Act as 'Archives of Preventive-Booster-Community-Vaccines' Against 'Any-'A-Z'-Diseases' By Immunizing Public-Health-Socio-Economy-Environment-Wildlife-Biodiversity-Conservation-S - Subhas Chandra Datta (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Introduction: Both the 1st-and 4th-pandemic outbreaks by SARS-CoV-2/3 causing COVID-19, starts in Wuhan, China, badly affecting human civilization with sever-post-COVID-diseases weakening the ability of COVID-19-vaccines to prevent-SARS-CoV-2/3-infection-or-reinfection with side effects. So, it will require proper COVID-booster-community-vaccines-doses to prevent 'Omicron' like any-'A-to-Z'-diseases as early-as-possible, fulfilling the main objectives of the current 'Community-Case-Study-Reports' are to find out the most suitable 'Biomedicines-Vaccine'.  Methods: The 'community-treatments' were done with the mixture-extract of spices; Ginger, Garlic, and Turmeric forming the high-diluted 'Spices-Community-Biomedicines' dissolving @ 5-10 drops / 50ml-100ml (a half to a full cup) of moderately hot drinking water, orally administered @ 3-5 times/day at an interval of 1- 2hrs, against naturally occurring coronavirus-infections-or re-infections, for 45-60 days, before-symptom-onset OR illness-onset (as a vaccine). Results: The present-oral-'community-treatments' of 'Spices-Community-Biomedicines-Physiology' are very-much-effective in controlling-diseases-by-boosting-natural-immunity-against coronavirus-2/3 with no side effects among the students and their parent's-community.  Conclusion: The present "Community-Treatments-Case-Study-Reports of Spices-Community-Biomedicines-Physiology Act as Archives of Preventive-Booster-Community-Vaccines Against Omicron-Like-Any-'A-to-Z'-Diseases By Immunizing Public-Health-Socio-Economy-Environment-Wildlife-Biodiversity-Conservation-Science-Technology-Communication-Applications-Ecology-Retaining-the-World-in-Old-Forms". And only 'Archives-community-biomedicines-physiology' may save the world.